History of the Recording of Folk Epics - Barno Mirzaeva (Researchparks Publishing, 2022)
The article discusses the research of the founder of Uzbek folklore, Khodi Zarifov, for the first time in the history of folklore, a live performance of Uzbek folk epics and folklore works of all genres was recorded, organized archival work, and will talk about research on creating the history of Uzbek folklore.